The Amplification of Common Somatic Symptoms by Posttraumatic Stress Disorder in Firefighters. Issue 2 (8th March 2017) - Milligan‐Saville, Josie S.; Paterson, Helen M.; Harkness, Emily L.; Marsh, Annabel M.; Dobson, Mark; Kemp, Richard I.; Bryant, Richard A.; Harvey, Samuel B.
Abstract : Posttraumatic stress disorder (PTSD) in emergency service personnel and other trauma‐exposed populations is known to be associated with a variety of physical health problems. However, little attention has been paid to the health of ageing emergency service personnel, who may be forced into early medical retirement because of a combination of these issues. Currently employed ( N = 274) Australian firefighters completed a cross‐sectional survey using validated, self‐report measures of PTSD and somatic symptoms. Analyses examined the association between probable PTSD and a range of common somatic symptoms, and whether any association differed depending on the age of the firefighters. Firefighters with PTSD reported greater levels of neurological ( p = .024), gastrointestinal ( p = .015), and cardiorespiratory ( p = .027) symptoms compared to those without PTSD. After adjusting for sex, age, and rank, linear regression analysis demonstrated that PTSD was significantly associated with increased total somatic symptom severity ( p = .024), with PTSD accounting for 9.8% of the variance in levels of somatic symptoms. There was no interaction between age and the association between PTSD and somatic symptom severity. These results suggest that PTSD is associated with a significant increase in a wide range of somatic symptoms among firefighters, regardless of age. The implications for the identification and treatment of PTSD are discussed.